Apelin and Vasopressin: The Yin and Yang of Water Balance - Girault-Sotias, Pierre-Emmanuel; Gerbier, Romain; Flahault, Adrien; de Mota, Nadia; Llorens-Cortes, Catherine (Frontiers in Endocrinology, 2021)
Apelin, a (neuro)vasoactive peptide, plays a prominent role in controlling body fluid homeostasis and cardiovascular functions. Experimental data performed in rodents have shown that apelin has an aquaretic effect via its central and renal actions. In the brain, apelin inhibits the phasic electrical activity of vasopressinergic neurons and the release of vasopressin from the posterior pituitary into the bloodstream and in the kidney, apelin regulates renal microcirculation and counteracts in the collecting duct, the antidiuretic effect of vasopressin occurring via the vasopressin receptor type 2. In humans and rodents, if plasma osmolality is increased by hypertonic saline infusion/water deprivation or decreased by water loading, plasma vasopressin and apelin are conversely regulated to maintain body fluid homeostasis. In patients with the syndrome of inappropriate antidiuresis, in which vasopressin hypersecretion leads to hyponatremia, the balance between apelin and vasopressin is significantly altered. In order to re-establish the correct balance, a metabolically stable apelin-17 analog, LIT01-196, was developed, to overcome the problem of the very short half-life (in the minute range) of apelin in vivo. In a rat experimental model of vasopressin-induced hyponatremia, subcutaneously (s.c.) administered LIT01-196 blocks the antidiuretic effect of vasopressin and the vasopressin-induced increase in urinary osmolality, and induces a progressive improvement in hyponatremia, suggesting that apelin receptor activation constitutes an original approach for hyponatremia treatment.